Movement patterns of small benthic fish in lowland headwater streams. (13th August 2013) - Mitsuo, Yoshito; Ohira, Mitsuru; Tsunoda, Hiroshi; Yuma, Masahide
Summary: Understanding the mechanism governing the movements of stream‐dwelling fish is a fundamental issue associated with a diverse range of ecological processes. We examined the movement pattern of a small benthic species, Lefua echigonia, using a mark–recapture technique in small headwater streams. Our main objectives were as follows: (i) to assess the movement range and direction of L .  echigonia ; (ii) to examine how biotic and abiotic factors affect emigration and immigration patterns and (iii) to assess movement patterns at the stream scale. Stationary fish accounted for the greatest proportion of recaptured adult L .  echigonia . Seventy‐five per cent of recaptured individuals moved <100 m in 12 months after release, and the maximum movement distance was 500 m upstream. Moreover, adult L .  echigonia showed significant upstream bias in movements. According to the results of the generalised linear mixed model GLMM analysis, movement of adult L .  echigonia was associated mainly with the density of conspecifics, rather than with habitat quality and body size. Adult L. echigonia were mainly stationary in relatively high‐density sections, and emigration tended to increase with decreasing density. Moreover, mobile individuals were prone to move into relatively high‐density sections. The proportion of mobile fish showed a strong positive correlation with catchment area at the stream scale. This result indicates that stream discharge can influence the mobility of adult L .  echigonia . During baseflow, the water was static in a number of stream sections, which suggests that the influence of catchment area on mobility may be more a function of freshets than normal water flow.